Open Source Software Solution for Small and Medium Enterprises - Reshad, Ahmad; Sinha, Shweta; Komal (International Journal of Computer Sciences and Engineering, 2020)
Information Technology is an enabler that brings flexibility to the business processes. Major factors to the successful adoption of Information Technology for Small and Medium Enterprises (SMEs) are the IT benefits and organizational culture, the selection and implementation of IT, and technical support. The paper discusses the selection and implementation of Open Source Software (OSS) and the technical support options, knowing which gives the SMEs better visibility at the IT adoption process. The paper also presents the implementation of selected OSS projects that can fulfill the common IT requirements of an SME, like Web server: to host and serve the web applications, Mail server: to facilitate the email messaging functionality within and outside of the SME, File server: to provide a space where the employees of an SME can store their files, and Backup server to copy the files, applications and/or databases of an SME and restore them in case of data loss.